Investments in electricity generating capacity under different market structures and with endogenously fixed demand - Anette Boom (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2003)
Investments in Generating Capacities between a monopolist and two competing firms are compared where the firms invest in their capacity and fix the retail price while electricity demand is uncertain. A unit price auction determines the wholesale electricity price when the firms compete. They know the level of demand when they bid their capacities. Total capacities can be larger or smaller with a duopoly than with a monopoly. If the two firms co-ordinate on a pareto dominant equilibrium, then the retail price is always higher and the social welfare lower in the competitive case, which exists only if capacity costs are not too high. – – Die Investitionen in Stromerzeugungskapazität von einem Monopolisten werden mit denen zweier konkurrierender Unternehmen verglichen. Dabei investieren die Unternehmen in ihre Kapazität und setzen ihren Einzelhandelspreis, bevor sich die unsichere Nachfrage realisiert hat. Im Falle konkurrierender Firmen bestimmt sich der Großhandelspreis in einer nicht-diskriminierenden Auktion. Die Unternehmen kennen die Nachfragerealisation, wenn sie dort Ihre Gebote abgeben. Die Gesamtkapazität im Duopol kann sowohl größer als auch kleiner sein als im Monopol. Falls die zwei Unternehmen sich jedoch auf ein paretodominantes Gleichgewicht koordinieren, dann ist der Einzelhandelspreis immer höher und die soziale Wohlfahrt immer niedriger im Wettbewerbsgleichgewicht als im Monopol, wobei ersteres nur bei relativ geringen Kapazitätskosten existiert.
Keywords: D42; D43; D44; L11; L12; L13; 330; Electricity Markets; Investments; Generating Capacities; Monopoly; Competition